The Violation of Copyright Music in the Form of Cover Song By Recording Through Social Media Related To Law Number 28 Of 2014 Concerning Copyright And Law Number 19 Of 2016 Regarding Electronic Transaction Information - uyan wiryadi (IHSA Institute, 2022)
The objectives of this study were to: 1) Determine whether cover songs that were recorded via social media violated Law Number 28 of 2014 Concerning Copyright in the sphere of music. 2) To identify the factors that contribute to copyright infringement when cover songs are recorded and shared on social media. This thesis was written using a statutory approach, specifically by analyzing the changes to Law Number 28 of 2014 concerning Copyright and its implications for copyright and its implementation by high state institutions and the Law of the Republic of Indonesia Number 19 of 2016 Regarding Amendments to Law Number 11 of 2008 Concerning Information and Electronic Transactions. The following are the findings of the author's research: It is a copyright infringement when someone performs a cover song on social media without permission from the artist, whether for non-commercial or commercial purposes. Among the factors influencing the occurrence of copyright infringement in Indonesia are: 1) Weak law enforcement against infringement violators. 2) Internet creations can be quickly replicated and spread internationally in a very short period of time and in big numbers. 3) There is no geographical restriction on the location of the perpetrator because a domain name or website can be viewed by anybody worldwide. 4) The procedure for inter-state events in dealing with copyright infringement on the internet, such as ascertaining who the perpetrator is and when the infringement happens (tempus delicti) and determining the legal region of the infringement (locus delicti), remains inconsistent.